Knockdown of FOXO6 inhibits cell proliferation and ECM accumulation in glomerular mesangial cells cultured under high glucose condition. Issue 3 (14th January 2019) - Wang, Yunqian; Xue, Lei; Li, Huicong; Shi, Jun; Chen, Baoping
Abstract : Forkhead box O 6 (FOXO6), a FOX transcription factor, has been found to be involved in diabetes mellitus and related complications. Abstract : Forkhead box O 6 (FOXO6), a FOX transcription factor, has been found to be involved in diabetes mellitus and related complications. However, the role of FOXO6 in diabetic nephropathy (DN) has not been fully understood. In the present study, we evaluated the functions of FOXO6 in high glucose (HG)-induced glomerular mesangial cells (MCs). The results showed that FOXO6 expression was significantly elevated in MCs after HG stimulation. Knockdown of FOXO6 by transfection with small interfering RNA (siRNA) targeting FOXO6 (siRNA-FOXO6) suppressed cell proliferation in MCs. The productions of extracellular matrix (ECM) components including collagen IV (Col IV) and fibronectin (FN) were markedly decreased after FOXO6 knockdown in MCs. Furthermore, knockdown of FOXO6 inhibited HG-induced activation of p38 MAPK signaling pathway in MCs. Collectively, these findings suggested that knockdown of FOXO6 inhibited cell proliferation and ECM accumulation in HG-induced MCs via inhibiting p38 MAPK signaling pathway. FOXO6 might be a beneficial therapeutic target for the prevention and treatment of DN.